Heterogeneous microenvironmental stiffness regulates pro-metastatic functions of breast cancer cells. (1st September 2021) - Liu, Chun; Li, Miao; Dong, Zhao-Xia; Jiang, Dong; Li, Xiaojing; Lin, Shuibin; Chen, Demeng; Zou, Xuenong; Zhang, Xing-Ding; Luker, Gary D.
Graphical abstract: Image, graphical abstract Abstract: Besides molecular and phenotypic variations observed in cancer cells, intratumoral heterogeneity also occurs in the tumor microenvironment. Correlative stiffness maps of different intratumor locations in breast tumor biopsies show that stiffness increases from core to periphery. However, how different local ECM stiffness regulates key functions of cancer cells in tumor progression remains unclear. Although increased tissue stiffness is an established driver of breast cancer progression, conclusions from 2D cultures do not correspond with newer data from cancer cells in 3D environments. Many past studies of breast cancer in 3D culture fail to recapitulate the stiffness of a real breast tumor or the various local stiffnesses present in a tumor microenvironment. In this study, we developed a series of collagen/alginate hybrid hydrogels with adjustable stiffness to match the core, middle, and peripheral zones of a breast tumor. We used this hydrogel system to investigate effects of different local stiffness on morphology, proliferation, and migration of breast cancer cells. RNA sequencing of cells in hydrogels with different stiffness revealed changes in multiple cellular processes underlying cancer progression, including angiogenesis and metabolism. We discovered that tumor cells in a soft environment enriched YAP1 and AP1 signaling related genes, whereas tumor cells in a stiff environment became more pro-angiogenic by upregulating fibronectin 1 (FN1) and matrix metalloproteinase 9 (MMP9) expression. This systematic study defines how the range of environmental stiffnesses present in a breast tumor regulates cancer cells, providing new insights into tumorigenesis and disease progression at the tumor-stroma interface. Statement of significance: Applied a well-defined hybrid hydrogel system to mimic the tumor microenvironment with heterogeneous local stiffness. Breast cancer cells tended to proliferate in soft core environment while migrate in stiff peripheral environment. Breast cancer cells shift from glycolysis to OXPHOS and fatty acid metabolism responding to stiff matrix microenvironment. The transcriptomic profile of breast cancer cells altered due to microenvironmental stiffness changes.